Dietary habits of lung cancer patients from the Lower Silesia region of Poland - Zabłocka-Słowińska, Katarzyna; Porębska, Irena; Gołecki, Marcin; Prescha, Anna; Pieczyńska, Joanna; Kosacka, Monika; Ilow, Rafał; Grajeta, Halina; Jankowska, Renata; Biernat, Jadwiga (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : Assessment of lung cancer patients’ dietary habits before treatment enable medical staff to provide more individual, precise and complex care to patients, taking into consideration their nutritional status. The aim of this study was, therefore, to evaluate dietary habits related to lung cancer risk of lung cancer patients in comparison with controls from the Lower Silesia region of Poland. Material and methods : Assessments of dietary habits, based on a validated questionnaire related to lung cancer risk were performed on 92 lung cancer patients and compared with the results obtained in 157 controls. Dietary patterns were evaluated concerning on eating frequency of high- and low- glycemic index products, vegetables and fruits, vegetable and fruit juices, green tea, liquid dairy products, meat and fried products over the previous year. Alcohol consumption was assessed on a dichotomous scale (yes or no). Results : Majority of patients had inappropriate dietary habits, such as low consumption of low GI cereal products, vegetables, fruit and green tea, and a high consumption frequency of fried products. Conclusions : Reported dietary mistakes indicate the need for dietary education among people at lung cancer risk and with newly diagnosed disease, to enhance their nutritional status.